Towards a Maqashid sharia-based conceptual framework of Islamic financial reporting in Indonesia: criticizing “Economic” decision usefulness objective - Birton, M. Nur A.; Sholihin, Mahfud (2018)
All the Conceptual Framework of Financial Reporting put economic decision-making usefulness the objective of financial reporting, including what so called as the Basic Framework for the Preparation and Presentation of Sharia Financial Statements (BFSFS) in Indonesia. BFSFS is the Indonesian conceptual framework adopted by the Indonesian Institute of Accountants (IAI) from the Framework for Preparation and Presentation Financial Statement International Accounting Standards Committee (IASC). Many criticisms are addressed to BFSFS because it is seen as carrying the interests of capitalism, imperialism and secularism. This article aims, first, to criticize the concept of "sharia principles" used as the foundation for the development of BFSFS in Indonesia; second, to criticize the use of decision usefulness concept as the main objective of sharia entity financial report adopted by BFSFS; third, to initiate maqashid sharia as the foundation of sharia Conceptual Framework of Financial Reporting development. In doing so we use criticism-reflective-constructivist approach.